Expansion devices for organic Rankine cycle (ORC) using in low temperature heat recovery: A review. (1st November 2019) - Zhao, Yuanyang; Liu, Guangbin; Li, Liansheng; Yang, Qichao; Tang, Bin; Liu, Yunxia
Highlights: Review of expansion devices studies for organic Rankine cycle (ORC) systems. Method to choose the types of expansion devices for ORC system. Turbines are suitable for the large-scale ORC systems. Screw expander are suitable for medium-scale ORC systems. The main technology trends for expansion devices are presented. Abstract: Studies and applications of organic Rankine cycle (ORC) systems are increasing in recent years because of the advantages of them on the recovery of low temperature heat sources. The choice of working fluids, system design methods, equipment, and applications of ORC systems were researched by many researchers. Expansion devices are the key equipment for ORC systems. The review of expansion devices for ORC systems was presented in this paper. The devices of scroll, screw, piston, vane, turbine, and ejector for ORC systems are involved. It is expected that the review presented here can summarize what was done before and will provide the investigator with the knowledge and ideas about how to choose and improve the performance of expansion devices for ORC systems.